The Effects of Air Pollutants, Particulate Matter 10 (PM10), Sulphur Dioxide (SO2) and Nitrogen Dioxide (NO2) on COVID-19 cases in Indonesia - Erwin Dariyanto (Sustainability Science and Resources, 2022)
This study aims to analyse the effects of air pollutants on the number of COVID-19 cases in Indonesia. Three pollutants, i.e. Particulate matter 10 (PM10), Sulphur dioxide (SO2) and Nitrogen dioxide (NO2), were analysed. The study covers a period of 1 March 2020 to 31 December 2020 involving data from the cities of Jakarta, Bandung, Yogyakarta, Semarang and Surabaya in Indonesia. This study used the Ordinary Least Square (OLS) method with the endurance test Robust Standard Errors. The regression results showed that PM10, SO2 and NO2 are statistically significant positive regressors of the number of COVID19 cases. Every 1 μg/m3 increase in PM10, SO2 and NO2 concentrations is shown to cause an additional 2.65, 7.96 and 21.01 cases of COVID-19, respectively. The implementation of Large-Scale Social Restrictions (PSBB) has a statistically significant impact in curbing COVID-19 transmission; reducing 447.4 cases of COVID-19.